2017
DOI: 10.1007/s10616-017-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

Seleno-short-chain chitosan induces apoptosis in human non-small-cell lung cancer A549 cells through ROS-mediated mitochondrial pathway

Abstract: Seleno-short-chain chitosan (SSCC) is a synthesized chitosan derivative. In this study, antitumor activity and underlying mechanism of SSCC on human non-small-cell lung cancer A549 cells were investigated in vitro. The MTT assay showed that SSCC could inhibit cell viability in a dose- and time-dependent manner, and 200 μg/ml SSCC exhibited significantly toxic effects on A549 cells. The cell cycle assay showed that SSCC triggered S phase cell cycle arrest in a dose- and time-dependent manner, which was related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The results were in agreement with our previous study that SSCC suppressed the growth of suspended human leukemia K562 and lung A549 cells and exhibited low toxic effect on normal mouse embryonic fibroblasts NIH3T3 and normal lung cells MRC-5. However, the most effective inhibition concentration of SSCC on K562 and A549 cells were 100 μg/ml and 200 μg/ml, separately, which may be associated with the type of tumor cells [28,32]. Thus, our results showed that SSCC could effectively inhibited breast cancer cells growth in vitro.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The results were in agreement with our previous study that SSCC suppressed the growth of suspended human leukemia K562 and lung A549 cells and exhibited low toxic effect on normal mouse embryonic fibroblasts NIH3T3 and normal lung cells MRC-5. However, the most effective inhibition concentration of SSCC on K562 and A549 cells were 100 μg/ml and 200 μg/ml, separately, which may be associated with the type of tumor cells [28,32]. Thus, our results showed that SSCC could effectively inhibited breast cancer cells growth in vitro.…”
Section: Discussionmentioning
confidence: 66%
“…As Michela et al [31] demonstrated that marine diatom cocconeis scutellum and eicosapentaenoic acid (EPA) contributed to proliferation inhibition and apoptosis of BT-20 cells in vitro. Seleno-short-chain chitosan (SSCC) was a synthesized seleno-short-chain chitosan with the molecular weight of 4826.986 Da [32]. In our previous studies, SSCC could induce apoptosis of leukemia K562 cells and lung cancer A549 cells in vitro [28,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Bcl-2 antagonizes Bax, so the high expression levels of Bcl-2 inhibitor block caspase-3-induced apoptosis. 38 These results indicate that CK promotes the downregulation of the Bcl-2/Bax ratio and the upregulation of caspase-3, inferring that CK-M can affect the apoptosis of NSCLC cells.…”
Section: Discussionmentioning
confidence: 68%
“…The uptake of these nanoparticles depends on the cell surface charge and the metabolic activity of cancerous cells [139]. Previous studies showed that blank CSNPs increased ROS concentration in cancerous cells, leading to mitochondrial cytochrome c release and apoptosis through the caspase cascade [140]. Recently, de Oliveira Junior et al [141] described, for the first time, the application of nanoparticle-mediated nose-to-brain delivery of melatonin for the treatment of GBM both in vitro and in vivo.…”
Section: In Vivo and Clinical Trial Evidence Of Melatonin Effects Agamentioning
confidence: 99%